Parenthood and Life Satisfaction in Stratified Labor Market: Evidence From Korea - Cho, Joonmo; Jung, Hanna (Frontiers in Public Health, 2022)
This study analyzes the effect of parenthood on life satisfaction with a stratified labor market using the Korean Labor and Income Study. For regular female workers at large companies, the decrease in life satisfaction due to parenthood is higher compared to that for men in a similar position due to the high opportunity cost of a career break following childbirth. For men who are non-regular employees at Small and medium-sized enterprises (SMEs), the effect of parenthood on life satisfaction is negative because they are the income earners of the family but earn a relatively low income at SMEs. Based on the results, the job characteristics of a stratified labor market have a significant influence on life satisfaction regarding parenthood. To enhance parental life satisfaction and raise the fertility rate, the structure of the stratified labor market needs to be changed so that the labor market becomes more flexible and includes a solid social safety net.